Click chemistry synthesis, stereocomplex formation, and enhanced thermal properties of well-defined poly(l-lactic acid)-b-poly(d-lactic acid) stereo diblock copolymers. Issue 6 (5th January 2017) - Han, Lili; Xie, Qing; Bao, Jianna; Shan, Guorong; Bao, Yongzhong; Pan, Pengju
Abstract : PLLA- b -PDLAs with well-controlled molecular weights, compositions, highly enhanced stereocomplexation ability, and thermal resistance were synthesized by ROP and click chemistry. Abstract : Stereoblock copolymerization of lactide enantiomers has been a feasible method to prepare stereocomplexed poly(lactic acid) (PLA) with highly improved thermal resistance. However, synthesis of high-molecular-weight (HMW) poly(l -lactic acid)- b -poly(d -lactic acid) (PLLA- b -PDLA) stereoblock copolymers with controlled stereoblock length and composition is still challenging. Herein we synthesized well-defined PLLA- b -PDLA stereo diblock copolymers with different molecular weights (MWs, 14–110 kDa) and PLLA and PDLA block lengths by a combination of ring-opening polymerization and azide/alkyne click chemistry. The crystallization kinetics, polymorphic crystalline structure, lamellar morphology, and thermomechanical properties of the PLLA- b -PDLAs were systematically investigated. All the PLLA- b -PDLAs exhibit fast crystallization and predominantly form stereocomplexes (SCs) during the cooling and heating processes. Symmetric PLLA- b -PDLAs with similar PLLA and PDLA block lengths exclusively crystallize in the SCs at all the investigated crystallization temperatures ( T c s) in melt crystallization; but asymmetric PLLA- b -PDLAs with very different PLLA and PDLA block lengths crystallize in both SCs and homocrystallites (HCs) at a low T c (<160 °C). Because of the formation of high-melting-point SCs, HMW PLLA- b -PDLAs exhibit better thermal resistance and higher storage moduli at a high temperature range (170–200 °C) than the homocrystalline PLLA.